2015
DOI: 10.1155/2015/793649
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine for the Management of Cervical Radiculopathy: An Overview of Systematic Reviews

Abstract: Background. Complementary and alternative medicine (CAM) is widely applied in the clinical practice of neck pain owing to cervical radiculopathy (CR). While many systematic reviews exist in CAM to improve CR, research is distributed across population, intervention, comparison, and setting. Objective. This overview aims to summarize the characteristics and evaluate critically the evidence from systematic reviews. Methods. A comprehensive literature search was performed in the six databases without language rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
(43 reference statements)
2
9
0
Order By: Relevance
“…Meanwhile, the effectiveness of integrative medicine for cervical radiculopathy and neck pain has been receiving wider recognition, giving lead to the recent surge of related studies [2326]. Unfortunately, most systematic reviews on integrative medicine for CDH and cervical radiculopathy report studies of low or moderate methodological quality [25], demonstrating the need for more definitive evidence generated through well-designed, rigorous clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the effectiveness of integrative medicine for cervical radiculopathy and neck pain has been receiving wider recognition, giving lead to the recent surge of related studies [2326]. Unfortunately, most systematic reviews on integrative medicine for CDH and cervical radiculopathy report studies of low or moderate methodological quality [25], demonstrating the need for more definitive evidence generated through well-designed, rigorous clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical spinal manipulation (CSM) is one of the important conservative treatments for symptomatic CDH [ 3 5 ]. Studies reported that CSM reduces pain in patients with symptomatic CDH [ 6 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, to get a balanced evaluation of an intervention, we emphasize here the crucial importance of the development of a standardized format for reporting adverse events in SRs. Finally, the methodology and quality of evidence from other SRs on TCM [ 37 39 ] were likewise problematic, which may suggest the deficiency of education or training for TCM researchers who conduct SRs and original clinical trials. We strongly recommend that relevant training should be provided to develop the TCM researchers’ consciousness and abilities in designing, conducting, and reporting TCM studies.…”
Section: Discussionmentioning
confidence: 99%